Pengaruh Pengungkapan Akuntansi Lingkungan dan Kinerja Keuangan Terhadap Nilai Perusahaan Farmasi yang Terdaftar di BEI 2018-2022 - Isrul Pati Sianturi; Thezar Fiqih Hidayat Hasibuan; Warsani Purnama Sari; Alfriado Leonard Noprian Dolok Saribu; Wardhani Indah Sari (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This study examines the effect of Environmental Accounting Disclosure and Financial Performance on the Value of Manufacturing Companies in the Pharmaceutical Industry Sub-Sector listed on the Indonesia Stock Exchange for the 2018-2022 period of 11 pharmaceutical companies. The sampling technique based on criteria using purposive sampling obtained 40 company annual report data. The data analysis method uses multiple linear regression analysis. Based on the regression results, it shows that environmental accounting disclosure has a positive and insignificant effect on company value and financial performance has a positive and significant effect on company value. Based on the simultaneous results, it is concluded that Environmental Accounting Disclosure and Financial Performance have a simultaneous and positive effect on the Value of Manufacturing Companies in the Pharmaceutical Industry Sub-Sector listed on the Indonesia Stock Exchange for the 2018-2022 period.